Kegiatan Pengabdian Masyarakat dalam Rangka Pencegahan Hiperurisemia Melalui Pemeriksaan Asam Urat Sejak Dini pada Masyarakat Kelurahan Grogol - Putra, Rosadi; Santoso, Alexander Halim; Gunaidi, Farell Christian; Dinali, Diana; Aziel, Disya Gwyneth (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
Uric acid (UA) is a waste product formed when the body breaks down purines, which are natural compounds found in the body and can be found in various types of foods such as alcohol, shellfish, and liver. Hyperuricemia is caused by increased uric acid production, decreased excretion, or a combination of both processes. Most people with hyperuricemia are asymptomatic (85% to 90%), but increased levels of uric acid in the blood or urine can cause gout or nephrolithiasis. Hyperuricemia and hyperuricosuria are also associated with other disorders such as metabolic syndrome, diabetes mellitus, cardiovascular disease, hypertension, atherosclerosis, obesity, and chronic kidney disease. The Community Service (PKM) activity held in Grogol Village, West Jakarta, aims to increase awareness of the elderly community regarding the importance of early detection of hyperuricemia. This program uses the Plan-Do-Check-Act (PDCA) approach, starting from planning uric acid level examinations and compiling educational materials, followed by implementing interactive screening and counseling, evaluating results, and following up in the form of medical referrals for participants with abnormal results. Of the 71 participants involved, only 1 person had uric acid levels above normal. Through education on low-purine diets, the importance of hydration, and physical exercise, this activity is expected to be able to reduce the incidence of hyperuricemia and its complications, as well as support the realization of a healthier elderly community that is aware of its metabolic health.